Preparation and surface coating method of carbon nanotube modified coating for improving surface flashover voltage of epoxy composite material

By doping 0.15 wt% carbon nanotube particles into the epoxy composite material and applying the surface, the problem of low flashover voltage along the surface of the epoxy composite material is solved, and the flashover voltage and the conductivity of the material are significantly improved, thus achieving the realization of the speedover voltage and the performance of the material. Improved DC flashover performance.

CN119286027APending Publication Date: 2025-01-10JILIN ELECTRIC POWER RES INST LTD +4
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411435486.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

At this stage, the flashover voltage of the epoxy composite material along the surface is low, resulting in a decrease in the insulation capacity of GIS equipment and a power outage accident in the power system. The long-term stability of the improvement effect of the existing technology is poor, and new technologies need to be developed to increase the DC flashover voltage.

Method used

The coating is prepared by mixing 0.15 wt% of carbon nanotube particles with epoxy resin, preheating, stirring, sonication and drying, and coating on the surface of the epoxy matrix. Form a modified insulating material to improve the surface conductivity and dielectric properties of the material.

Benefits of technology

It significantly improves the DC flashover voltage along the surface of the epoxy composite material, reduces the trap energy level of the insulating material, promotes carrier migration, accelerates the potential attenuation of the material surface, and increases the flashover voltage. The process is low and easy to process Strong operationality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286027A_ABST
    Figure CN119286027A_ABST
Patent Text Reader

Abstract

A preparation and surface coating method of a carbon nanotube modified coating for improving surface flashover voltage of an epoxy composite material belongs to the field of high-voltage insulating materials, and comprises the following steps: weighing preheated epoxy resin and anhydride curing agent according to a ratio, putting into an oil bath environment, stirring, adding an accelerant, and continuously stirring; the defoamed solution is poured into a mold and placed in a drying oven for multi-stage heating curing, and an epoxy matrix is obtained; mixing the dried 0.15 wt% of carbon nanotube particles with an anhydride curing agent, and then carrying out mixed ultrasonic treatment by adopting an ultrasonic instrument; adding the preheated epoxy resin into a mixture of the carbon nanotube particles and the anhydride curing agent, stirring, adding an accelerant, continuously stirring, and carrying out vacuum defoaming, so as to obtain a coating material; and coating the surface of an epoxy matrix with the coating material, and putting the epoxy matrix into a drying oven for multi-stage drying and curing to obtain the insulating material coated with the surfaces of the epoxy / carbon nanotube particles. According to the method provided by the invention, the surface electric field distortion can be obviously reduced, and a foundation is laid for improving the direct-current surface flashover performance of the insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-voltage insulating materials, and in particular relates to a method for preparing a carbon nanotube modified coating for improving the surface flashover voltage of an epoxy composite material and a surface coating method. Background Art

[0002] Since the voltage of flashover at the gas-solid interface is much lower than the breakdown voltage of gas and solid at the same gap, the surface flashover of the basin-type insulator of GIS equipment has become one of the engineering problems that need to be solved urgently in the current stage of UHV DC transmission. The surface flashover of the gas-solid interface will release a large amount of sound, heat and light energy, which will ablate the surface of the insulator, causing a significant decrease in the surface insulation capacity, and then cause power outages in the power system, seriously affecting the normal production order of society and endangering economic development. The main material of basin-type insulators is epoxy resin. Therefore, exploring effective technologies to improve the surface flashover voltage of epoxy composite materials is of great significance to the further development of UHV transmission technology.

[0003] At present, the main method to improve the surface flashover performance of epoxy composite materials is to increase the surface charge dissipation rate and surface flashover voltage by enhancing the surface conductivity of the material. Common methods include fluorination and plasma treatment. Although these surface treatment technologies can improve the flashover voltage to a certain extent, the long-term stability of the treatment effect is poor, so new technologies are urgently needed. Carbon nanotubes, as an emerging material, can greatly regulate the conductivity of polymer materials. Therefore, a certain proportion of epoxy / carbon nanotube coating can be prepared and coated on the surface of the insulator to regulate the surface conductivity, reduce the accumulation of surface charge, and achieve the effect of increasing the DC flashover voltage. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a carbon nanotube modified coating and surface coating for improving the surface flashover voltage of epoxy composite materials. Compared with the conventional uncoated epoxy resin, the present invention can improve the DC surface flashover voltage of epoxy resin. By doping the insulating material with 0.15wt% carbon nanotube particles by mass fraction, compared with the unmodified epoxy resin, the trap energy level of the insulating material is reduced, the shallow trap density of the insulating material is increased, the migration of carriers is promoted, the potential decay of the material surface is accelerated, the surface conductivity of the material is increased, and the flashover voltage is increased. It can lay a foundation for the engineering application of nanocomposite materials, and the process difficulty is low and the operability is strong.

[0005] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a carbon nanotube modified coating and a surface coating method for improving the surface flashover voltage of an epoxy composite material, comprising the following steps:

[0006] 1) preheating the carbon nanotube particles, epoxy resin and anhydride curing agent respectively and setting them aside;

[0007] 2) Weigh the preheated epoxy resin and anhydride curing agent according to a preset ratio and pour them into a three-necked flask;

[0008] 3) placing the three-necked flask containing the mixture in step 2) into an oil bath and stirring to uniformly disperse the mixture;

[0009] 4) adding the accelerator to the mixture obtained in step 3) and continuing stirring to make the solution completely mixed;

[0010] 5) pouring the mixture obtained in step 4) into a mold and placing it in an oven for multi-stage heating and curing to obtain an epoxy matrix;

[0011] 6) placing the epoxy matrix cured in step 5) in a desiccator for later use;

[0012] 7) mixing the preheated carbon nanotube particles and the acid anhydride curing agent and then mixing and ultrasonicating the mixture using an ultrasonic device to make the mixture uniformly dispersed;

[0013] 8) adding the preheated epoxy resin to the mixture obtained in step 7), and placing the newly obtained mixture in an oil bath environment and stirring;

[0014] 9) adding a promoter to the mixture obtained in step 8), continuing stirring and vacuum degassing to obtain an epoxy / carbon nanotube coating;

[0015] 10) coating the epoxy / carbon nanotube coating obtained in step 9) on the surface of the epoxy matrix obtained in step 6) to form a coating layer after filling the surface of the epoxy matrix, and placing the coating layer in an oven for multi-stage drying and curing to obtain an insulating material coated with epoxy / carbon nanotubes;

[0016] The total mass percentage of the carbon nanotube particles, epoxy resin, anhydride curing agent and accelerator is 100%, wherein the mass fraction of the carbon nanotube particles is 0.15wt%.

[0017] Furthermore, in step 1), the preheating temperature of the carbon nanotube particles is 95°C to 105°C, the time is 11h to 13h, and the particle size of the carbon nanotubes is 2nm to 20nm in diameter and 10um to 20um in length; the preheating temperature of the epoxy resin and the anhydride curing agent is 50°C to 60°C, the time is 6h to 8h, the epoxy resin adopts bisphenol A type liquid epoxy resin, and the anhydride curing agent adopts liquid methyltetrahydrophthalic anhydride.

[0018] Furthermore, it is characterized in that in step 2), the mass fraction ratio of the epoxy resin and the methyltetrahydrophthalic anhydride curing agent is (98-102):(78-82).

[0019] Furthermore, in step 3), the heating temperature of the oil bath environment is 77° C. to 83° C., the heating time and stirring time are 37 min to 43 min, and the stirring speed is 77 rad / min to 83 rad / min.

[0020] Furthermore, in step 4), the mass fraction of the accelerator is 0.95% to 1.05% of the total mass fraction, the accelerator used is 2,4,6-tris(dimethylaminomethyl)phenol, the heating time and stirring time are 7min to 13min, and the stirrer speed is 77rad / min to 83rad / min.

[0021] Furthermore, the multi-stage heating procedure in step 5) is as follows: first, the temperature is raised to 77°C to 83°C and kept warm for 3.9h to 4.1h, then the temperature is raised to 117°C to 123°C and kept warm for 7.9h to 8.1h. The mold used is a circular mold with a diameter of 49.9h to 50.1h and a thickness of 0.99mm to 1.01mm.

[0022] Furthermore, in step 7), the ultrasonic time is 1.9 h to 2.1 h, each ultrasonic time is 0.4 h to 0.6 h, and the interval between each ultrasonic time is 8 min to 12 min.

[0023] Furthermore, in step 8), the heating temperature of the oil bath environment is 77° C. to 83° C., the heating time and stirring time are 37 min to 43 min, and the stirring speed is 77 rad / min to 83 rad / min.

[0024] Furthermore, in step 9), the mass fraction of the accelerator is 0.95% to 1.05% of the total mass fraction, the accelerator used is 2,4,6-tris(dimethylaminomethyl)phenol, and the heating time and stirring time are 7 min to 13 min.

[0025] Furthermore, the heating procedure in step 10) is specifically as follows: heating to 117° C. to 123° C. and keeping warm for 11.9 h to 12.1 h.

[0026] Compared with the prior art, the present invention has the following beneficial technical effects:

[0027] The present invention coats and modifies epoxy materials by a method of doping carbon nanotube particles. By doping conductive nanoparticles, the electrical characteristics and dielectric properties of the prepared composite insulating material are greatly changed. After 0.15wt% of carbon nanotube particles are doped into epoxy resin, the dielectric constant and polarization properties of the epoxy composite material are improved due to the interface effect of the carbon nanotubes and the epoxy resin. After doping with 0.15wt% of carbon nanotube particles, the deep traps of the epoxy composite material become shallower, the trap energy level decreases, and the shallow trap density increases, resulting in an increase in the surface conductivity of the material, indicating that the carbon nanotube modification allows the epoxy resin material to introduce more shallow traps, accelerates the migration of carriers, and helps to improve the surface flashover performance of the material.

[0028] The results of DC surface flashover show that compared with the uncoated epoxy sample, the surface flashover voltage of the sample with 0.15wt% carbon nanotubes added is increased by 12%. By coating the epoxy / carbon nanotube material, the shallow trap density on the surface of the dielectric material increases, and the decrease in the trap depth makes it easier for carriers to escape when excited by the electric field. Therefore, the surface charge migration is easier, the surface charge accumulation is reduced, and the DC flashover voltage is increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings in the specification are used to provide further understanding of the present invention and constitute a part of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0030] Figure 1 Surface potential distribution diagrams of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3;

[0031] Figure 2 The trap energy level diagrams of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3;

[0032] Figure 3 The dielectric constant diagrams of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3;

[0033] Figure 4 Surface conductivity diagrams of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3;

[0034] Figure 5 The Weibull distribution diagram of the DC surface flashover voltage of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3.

[0035] Figure 6 The characteristic voltage distribution diagram of the DC surface flashover voltage of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a carbon nanotube modified coating and a surface coating method for improving the surface flashover voltage of an epoxy composite material, comprising the following steps:

[0037] 1) Preheating and drying the carbon nanotube particles in an oven for 11 h to 13 h at a temperature range of 95° C. to 105° C.; preheating the epoxy resin and the acid anhydride curing agent in an oven to reduce the viscosity of the liquid and improve the fluidity of the liquid, with a preheating time of 6 h to 8 h and a preheating temperature range of 50° C. to 60° C.

[0038] 2) The epoxy resin is WSR618 (E-51) bisphenol A liquid epoxy resin produced by Nantong Xingchen Synthetic Materials Co., Ltd., the anhydride curing agent is GH9303 liquid methyltetrahydrophthalic anhydride produced by Jiaxing Dongfang Chemical Plant, and the accelerator used in the present invention is 2,4,6-tris (dimethylaminomethyl) phenol produced by Kunshan Jiuli Electronic Materials Co., Ltd.; the particle size of the carbon nanotube particles is 2nm to 20nm, and the length is 10um to 20um. The stirrer used in the oil bath is a THINKY stirrer produced by Shinki Trading of Japan.

[0039] 3) Stir the epoxy resin and anhydride curing agent in a three-necked flask in an oil bath at 77° C. to 83° C. and 77 rad / min to 83 rad / min for 37 min to 43 min.

[0040] 4) After stirring, add an accelerator to the container containing the mixed solution, and continue stirring at the same heating temperature and stirring speed as step 3) for 7 minutes to 13 minutes.

[0041] 5) The stirred mixed solution is slowly poured into a circular mold with a diameter of 49.9 mm to 50.1 mm and a depth of 0.99 mm to 1.01 mm, and multi-stage drying is performed in an oven. The multi-stage drying procedure is firstly to heat to 77° C. to 83° C. and keep warm for 3.9 h to 4.1 h, and then to heat to 117° C. to 123° C. and keep warm for 7.9 h to 8.1 h to prepare an epoxy matrix.

[0042] 6) The carbon nanotube particles dried for 12±1h were ultrasonically treated for 1.9h~2.1h, with each ultrasonic treatment lasting 0.4h~0.6h and an interval of 8min~12min in between. 0.05wt%, 0.15wt%, and 0.25wt% of carbon nanotube particles were mixed in methyltetrahydrophthalic anhydride and epoxy resin, and the mixed solution was stirred under the same conditions for 37min~43min.

[0043] 7) After stirring, add a promoter to the container where the carbon nanotube particles are completely dispersed, and continue stirring under the same conditions for 7 minutes to 13 minutes.

[0044] 8) After slowly pouring the solution containing carbon nanotube particles onto the surface of the pre-made epoxy matrix, the composite material with the carbon nanotube particle coating layer is cured in an oven at a temperature of 117° C. to 123° C. for 11.9 h to 12.1 h.

[0045] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0046] The following detailed description is the description of the embodiments, and is intended to provide further detailed description of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used in the present invention are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present invention.

[0047] Example 1

[0048] 1. Matrix Preparation

[0049] 1) 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h and 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h were mixed in a three-necked flask to obtain a mixed solution A of epoxy resin and methyltetrahydrophthalic anhydride.

[0050] 2) The mixed solution A was stirred at a constant temperature of 80° C. for 40 min at a rotation speed of 80 rad / min using a THINKY stirrer.

[0051] 3) Add 2,4,6-tris(dimethylaminomethyl)phenol as an accelerator to the mixture obtained in step 2), and stir with a THINKY mixer for 10 minutes to obtain an epoxy coating. Slowly pour the epoxy coating into a circular mold with a diameter of 50 mm and a depth of 1.0 mm, and send the mold into an oven for curing at 80° C. for 4 hours and at 120° C. for 8 hours to obtain an epoxy matrix.

[0052] 2. Coating Preparation

[0053] 1) 0.050 g of carbon nanotube particles preheated at 100° C. for 12 h and 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h were mixed in a three-necked flask to form a suspension; the mixture of carbon nanotube particles and methyltetrahydrophthalic anhydride was fully and uniformly dispersed by ultrasonication for 2 h, each time for 0.5 h, with an interval of 10 min.

[0054] 2) The obtained carbon nanotube particle / methyltetrahydrophthalic anhydride mixed solution was mixed with 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h in a three-necked flask to obtain a mixed solution of the three substances.

[0055] 3) The mixed solution in step 2) was stirred at a constant temperature of 80° C. for 40 min at a speed of 80 rad / min using a THINKY stirrer.

[0056] 4) Add 2,4,6-tris(dimethylaminomethyl)phenol as a promoter to the mixture obtained in step 3), and stir the mixture using a THINKY stirrer under the same oil bath environment and rotation speed conditions to obtain an epoxy / carbon nanotube coating for 10 minutes.

[0057] Finally, the epoxy / carbon nanotube coating was slowly poured onto the epoxy substrate surface using a container. After the coating filled the surface, it was placed in an oven at 120° C. for curing for 12 h.

[0058] The total mass percentage of the carbon nanotube particles, epoxy resin, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100%, wherein the mass fraction of the carbon nanotubes is 0.15wt%, and the mass ratio of the epoxy resin, the acid anhydride curing agent and the accelerator is 100:80:1.

[0059] Example 2: Minimize the variables such as temperature, time, and speed

[0060] 1. Matrix Preparation

[0061] 1) 22.22 g of methyltetrahydrophthalic anhydride preheated at 50° C. for 6 h and 27.77 g of bisphenol A type liquid epoxy resin preheated at 50° C. for 6 h were mixed in a three-necked flask to obtain a mixed solution A of epoxy resin and methyltetrahydrophthalic anhydride.

[0062] 2) The mixed solution A was stirred at a constant temperature of 77° C. for 37 min at a rotation speed of 77 rad / min using a THINKY stirrer.

[0063] 3) Add 2,4,6-tris(dimethylaminomethyl)phenol to the mixture obtained in step 2) and stir with a THINKY mixer for 7 minutes to obtain an epoxy coating. Slowly pour the epoxy coating into a circular mold with a diameter of 49.9 mm and a depth of 0.09 mm, and send the mold into an oven for curing at 77°C for 3.9 hours and at 117°C for 7.9 hours to obtain an epoxy matrix.

[0064] 2. Coating Preparation

[0065] 1) 0.050 g of carbon nanotube particles preheated to 95° C. for 11 h and 22.22 g of methyltetrahydrophthalic anhydride preheated to 50° C. for 6 h were mixed in a three-necked flask to form a suspension; the mixture of carbon nanotube particles and methyltetrahydrophthalic anhydride was fully and uniformly dispersed by ultrasonication for 1.9 h, with each ultrasonication lasting 0.4 h and an interval of 8 min.

[0066] 2) The obtained carbon nanotube particle / methyltetrahydrophthalic anhydride mixed solution was mixed with 27.77 g of bisphenol A type liquid epoxy resin preheated at 50° C. for 6 h in a three-necked flask to obtain a mixed solution of the three substances.

[0067] 3) The mixed solution in step 2) was stirred at a constant temperature of 77° C. for 37 min at a rotation speed of 77 rad / min using a THINKY stirrer.

[0068] 4) Add 2,4,6-tris(dimethylaminomethyl)phenol as a promoter to the mixture obtained in step 3), and stir the mixture using a THINKY stirrer under the same oil bath environment and rotation speed conditions as in step 3) to obtain an epoxy / carbon nanotube coating for 7 minutes.

[0069] Finally, the coating material was slowly poured onto the epoxy resin surface using a container. After the coating filled the surface, it was placed in an oven at 117°C for curing for 11.9 hours.

[0070] The total mass percentage of the carbon nanotube particles, epoxy resin, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100%, wherein the mass fraction of the carbon nanotubes is 0.15wt%, and the mass ratio of the epoxy resin, the acid anhydride curing agent and the accelerator is 98:78:0.95.

[0071] Example 3: Maximizing the variables of temperature, time, speed, etc.

[0072] 1. Matrix Preparation

[0073] 1) 22.22 g of methyltetrahydrophthalic anhydride preheated at 60° C. for 8 h and 27.77 g of bisphenol A type liquid epoxy resin preheated at 60° C. for 8 h were mixed in a three-necked flask to obtain a mixed solution A of epoxy resin and methyltetrahydrophthalic anhydride.

[0074] 2) The mixed solution A was stirred at a constant temperature of 83° C. for 43 min at a rotation speed of 83 rad / min using a THINKY stirrer.

[0075] 3) Add 2,4,6-tris(dimethylaminomethyl)phenol to the mixture obtained in step 2) and stir with a THINKY mixer for 13 minutes to obtain an epoxy coating. Slowly pour the epoxy coating into a circular mold with a diameter of 50.1 mm and a depth of 1.01 mm, and send the mold into an oven for curing at 83°C for 4.1 hours and at 123°C for 8.1 hours to obtain an epoxy matrix.

[0076] 2. Coating Preparation

[0077] 1) 0.050 g of carbon nanotube particles preheated to 105° C. for 13 h and 22.22 g of methyltetrahydrophthalic anhydride preheated to 60° C. for 8 h were mixed in a three-necked flask to form a suspension; the mixture of carbon nanotube particles and methyltetrahydrophthalic anhydride was fully and uniformly dispersed by ultrasonication for 2.1 h, with each ultrasonication lasting 0.6 h and an interval of 12 min.

[0078] 2) The obtained carbon nanotube particle / methyltetrahydrophthalic anhydride mixed solution was mixed with 27.77 g of bisphenol A type liquid epoxy resin preheated at 60° C. for 8 h in a three-necked flask to obtain a mixed solution of the three substances.

[0079] 3) The mixed solution in step 2) was stirred at a constant temperature of 83° C. for 43 min at a rotation speed of 83 rad / min using a THINKY stirrer.

[0080] 4) Add 2,4,6-tris(dimethylaminomethyl)phenol to the mixture obtained in step 3), and stir it with a THINKY stirrer under the same oil bath environment and rotation speed conditions as in step 3) to obtain an epoxy / carbon nanotube coating for 13 minutes.

[0081] Finally, use a container to slowly pour the coating material onto the surface of the epoxy resin. After the coating fills the surface, put it into an oven at 123°C for curing for 12.1 hours.

[0082] The total mass percentage of the carbon nanotube particles, epoxy resin, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100%, wherein the mass fraction of the carbon nanotubes is 0.15wt%, and the mass ratio of the epoxy resin, the acid anhydride curing agent and the accelerator is 102:82:1.05.

[0083] Comparative Example 1: Epoxy resin material

[0084] The specific method is:

[0085] 1) 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h and 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h were mixed in a three-necked flask to obtain a mixed solution A of epoxy resin and methyltetrahydrophthalic anhydride.

[0086] 2) The mixed solution A was stirred at a constant temperature of 80° C. for 40 min at a rotation speed of 80 rad / min using a THINKY stirrer.

[0087] 3) Add 2,4,6-tris(dimethylaminomethyl)phenol accelerator to the mixture obtained in 2), and stir at a constant temperature of 80°C for 10 minutes at a speed of 80 rad / min using a THINKY mixer. Slowly pour the mixed solution into the mold, and send the mold into an oven for curing at 80°C for 4 hours and at 120°C for 8 hours to obtain an epoxy resin material.

[0088] The total mass percentage of the carbon nanotube particles, epoxy resin, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100%, wherein the mass ratio of the epoxy resin, the acid anhydride curing agent and the accelerator is 100:80:1.

[0089] Comparative Example 2: Epoxy resin / 0.05%wt carbon nanotube nanoparticle surface coating material

[0090] The specific method is:

[0091] 1. Matrix Preparation

[0092] 1) 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h and 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h were mixed in a three-necked flask to obtain a mixed solution A of epoxy resin and methyltetrahydrophthalic anhydride.

[0093] 2) The mixed solution A was stirred at a constant temperature of 80° C. for 40 min at a rotation speed of 80 rad / min using a THINKY stirrer.

[0094] 3) Add the mixture obtained in 2) and stir it with a THINKY mixer for 10 minutes to obtain an epoxy coating. Slowly pour the epoxy coating into a circular mold with a diameter of 50 mm and a depth of 1.0 mm, and send the mold into an oven for curing at 80° C. for 4 hours and at 120° C. for 8 hours to obtain an epoxy matrix.

[0095] 2. Coating Preparation

[0096] 1) 0.025 g of carbon nanotube particles preheated at 100° C. for 12 h and 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h were mixed in a three-necked flask to form a suspension; the mixture of carbon nanotube particles and methyltetrahydrophthalic anhydride was fully and uniformly dispersed by ultrasonication for 2 h, each time for 0.5 h, with an interval of 10 min.

[0097] 2) The obtained carbon nanotube particle / methyltetrahydrophthalic anhydride mixed solution was mixed with 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h in a three-necked flask to obtain a mixed solution of the three substances.

[0098] 3) The mixed solution in step 2) was stirred at a constant temperature of 80° C. for 40 min at a speed of 80 rad / min using a THINKY stirrer.

[0099] 4) Add 2,4,6-tris(dimethylaminomethyl)phenol to the mixture obtained in 3), and stir it with a THINKY stirrer in the same oil bath environment and speed conditions as in step 3) for 10 minutes to obtain an epoxy / carbon nanotube coating.

[0100] Finally, use a container to slowly pour the coating material onto the surface of the epoxy resin. After the coating fills the surface, put it into an oven at 120°C for curing for 12 hours.

[0101] The total mass percentage of the carbon nanotube particles, epoxy resin, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100%, wherein the mass fraction of the carbon nanotubes is 0.05%, and the mass ratio of the epoxy resin, the acid anhydride curing agent and the accelerator is 100:80:1.

[0102] Comparative Example 3: Epoxy resin / 0.25%wt carbon nanotube nanoparticle surface coating material

[0103] The specific method is:

[0104] 1. Matrix Preparation

[0105] 1) 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h and 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h were mixed in a three-necked flask to obtain a mixed solution A of epoxy resin and methyltetrahydrophthalic anhydride.

[0106] 2) The mixed solution A was stirred at a constant temperature of 80° C. for 40 min at a rotation speed of 80 rad / min using a THINKY stirrer.

[0107] 3) Add 2,4,6-tris(dimethylaminomethyl)phenol to the mixture obtained in 2) and stir with a THINKY mixer for 10 minutes to obtain an epoxy coating. Slowly pour the epoxy coating into a circular mold with a diameter of 50 mm and a depth of 1.0 mm, and send the mold into an oven for curing at 80° C. for 4 hours and at 120° C. for 8 hours to obtain an epoxy matrix.

[0108] 2. Coating Preparation

[0109] 1) 0.075 g of carbon nanotube particles preheated at 100° C. for 12 h and 22.22 g of methyltetrahydrophthalic anhydride preheated at 55° C. for 7 h were mixed in a three-necked flask to form a suspension; the mixture of carbon nanotube particles and methyltetrahydrophthalic anhydride was fully and uniformly dispersed by ultrasonication for 2 h, each time for 0.5 h, with an interval of 10 min.

[0110] 2) The obtained carbon nanotube particle / methyltetrahydrophthalic anhydride mixed solution was mixed with 27.77 g of bisphenol A type liquid epoxy resin preheated at 55° C. for 7 h in a three-necked flask to obtain a mixed solution of the three substances.

[0111] 3) The mixed solution in step 2) was stirred at a constant temperature of 80° C. for 40 min at a speed of 80 rad / min using a THINKY stirrer.

[0112] 4) Add 2,4,6-tris(dimethylaminomethyl)phenol to the mixture obtained in step 3), and stir the mixture in the same oil bath environment and rotation speed as step 3) using a THINKY stirrer for 10 minutes to obtain an epoxy / carbon nanotube coating.

[0113] Finally, use a container to slowly pour the coating material onto the surface of the epoxy resin. After the coating fills the surface, put it into an oven at 120°C for curing for 12 hours.

[0114] The total mass percentage of the carbon nanotube particles, epoxy resin, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100%, wherein the mass fraction of the carbon nanotubes is 0.05%, and the mass ratio of the epoxy resin, the acid anhydride curing agent and the accelerator is 100:80:1.

[0115] The dielectric constant reflects the polarization phenomenon of the material. As the frequency increases, the dielectric constant of the same sample decreases. This is mainly due to the fact that the relaxation polarization inside the material cannot keep up with the change in frequency. The epoxy / carbon nanotube coating material doped with 0.15wt% makes it easier for charges to migrate on the surface of the material through the folding effect of the molecular chain inside the material, resulting in an increase in the dielectric constant of the composite material. The specific dielectric constants of Example 1 and Comparative Examples 1, 2, and 3 at different frequencies at 20°C are shown in Table 1.

[0116] Table 1 Dielectric constants of samples of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3

[0117] Sample model Comparative Example 1 Comparative Example 2 Comparative Example 3 Example 1 0.10Hz 3.635 4.029 4.429 4.135 1.00Hz 3.629 3.983 4.383 4.129 50.00Hz 3.606 3.906 4.306 4.106 100.00Hz 3.602 3.905 4.302 4.102 2000.00Hz 3.579 3.855 4.255 4.079 10000.00Hz 3.559 3.826 4.226 4.059

[0118] Figure 3The dielectric constant of the comparative example and the example at 20°C varies with the frequency. The dielectric constant of the coating material doped with 0.15wt% carbon nanotubes (Example 1) is significantly increased compared with that of the comparative example 1. Due to the conductivity of the carbon nanotubes, the dielectric constant of the interface area where the carbon nanotube particles and the epoxy matrix are connected increases significantly, resulting in an increase in the dielectric constant of the coated insulating material.

[0119] The surface potential decay time of pure epoxy resin and carbon nanotube / epoxy resin composite samples was measured. The experimental process used a needle plate electrode with an electrode spacing of 3mm to charge the material surface. After charging for 10 minutes, the electrostatic probe was used to measure the potential data on the material surface, and the program was used to record the point decay of the material surface within 14000s. The surface potential of the material surface was used to invert the trap energy level. The experimental results are shown in Figure 1 and Figure 2 The decay rate of the epoxy resin coated material doped with 0.15 wt% carbon nanotubes (Example 1) is higher than that of the ordinary unmodified epoxy resin, indicating that the migration of the material carrier current is increased by coating the carbon nanotube particles, and the shallow trap energy level is reduced from 1.03 eV in Comparative Example 1 to 0.96 eV in the example.

[0120] The DC surface flashover test in air was conducted on pure epoxy resin and carbon nanotube / epoxy resin composite samples. During the experiment, stainless steel finger electrodes were used with an electrode spacing of 8mm and the air environment was at room temperature and pressure. In the DC flashover experiment, a step-by-step pressurization method was adopted. The sample was pressurized from 5kV and the voltage was increased by 1kV until the sample flashed stably and the flashover voltage was recorded. Table 2 shows the measurement results of the DC surface flashover voltage in air.

[0121] Table 2 Measurement results of DC surface flashover voltage of samples in air

[0122]

[0123]

[0124] It can be seen from Table 2 that doping with carbon nanotube nanoparticles helps to improve the DC surface flashover performance of epoxy resin in air. The flashover voltage is greatly improved when the epoxy surface is coated with carbon nanotube material. The Weibull distribution diagram of the surface flashover voltage of the embodiment and the comparative example is shown in FIG. Figure 5 .

[0125] from Figure 5 and Figure 6It can be seen that with the increase of coating concentration, the DC flashover voltage first increases and then decreases. By extracting the characteristic voltage in the Weibull distribution, it can be found that the DC surface flashover Weibull characteristic voltage is from large to small: Comparative Example 1 (14.65kV), Comparative Example 2 (16.56kV), Comparative Example 3 (16.28kV), Example (17.71kV), and the surface flashover voltage of the epoxy / carbon nanotube sample with 0.15wt% nanoparticles added is increased by 12%. By doping nanoparticles with 0.15wt%, the migration of carriers is promoted, the charge dissipation on the surface of the material is accelerated, and the tangential electric field distortion is reduced. Reducing the doping concentration will cause the electric field to be distorted due to the introduction of more deep traps in the interface area, making it more likely to flashover. However, increasing the doping concentration will cause obvious leakage current on the surface of the material, resulting in a decrease in the flashover voltage.

[0126] For the surface conductivity test, the comparative and example samples were placed in a resistivity box and the current was measured using an electrometer. 1 kV mm -1 Conduct 5 tests on each type of sample to obtain the average value and calculate the conductivity. The surface conductivity is as follows: Figure 4 shown. Figure 4 It can be seen that the conductivity of nanoparticles coated with a small amount of epoxy material decreases. The surface conductivity of Comparative Example 1 is 4.23×10 -15 S, the surface conductivity of comparative example 2 is 5.1×10 -16 S, the surface conductivity of comparative example 3 is 7.68×10 -12 S, the surface conductivity of Example 1 is 8.94×10 -14 S, it can be seen that the conductivity of a small amount of doped nanoparticles decreases, and when the number of nanoparticles in the epoxy resin coating layer increases, the conductivity increases. When the coating concentration of epoxy / carbon nanotubes is 0.15wt%, the conductivity increases by 1 order of magnitude. This is because there are a large number of deep traps in the interface area between a small amount of coated carbon nanotubes and epoxy, which inhibit the migration of carriers. When the coating content of carbon nanotubes increases, the interface area overlaps, which promotes the migration of carriers.

[0127] The embodiments described above are only preferred technical solutions of the present invention and should not be regarded as limitations of the present invention. The embodiments and features in the embodiments of the present application can be arbitrarily combined with each other without conflict. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. A method for preparing a carbon nanotube modified coating and applying the coating on the surface to improve the surface flashover voltage of epoxy composite materials, characterized in that: The following steps are involved: 1) preheating the carbon nanotube particles, epoxy resin and anhydride curing agent respectively and setting them aside; 2) Weigh the preheated epoxy resin and anhydride curing agent according to a preset ratio and pour them into a three-necked flask; 3) placing the three-necked flask containing the mixture in step 2) into an oil bath and stirring to uniformly disperse the mixture; 4) adding the accelerator to the mixture obtained in step 3) and continuing stirring to make the solution completely mixed; 5) pouring the mixture obtained in step 4) into a mold and placing it in an oven for multi-stage heating and curing to obtain an epoxy matrix; 6) placing the epoxy matrix cured in step 5) in a desiccator for later use; 7) mixing the preheated carbon nanotube particles and the acid anhydride curing agent and then mixing and ultrasonicating the mixture using an ultrasonic device to make the mixture uniformly dispersed; 8) adding the preheated epoxy resin to the mixture obtained in step 7), and placing the newly obtained mixture in an oil bath environment and stirring; 9) adding a promoter to the mixture obtained in step 8), continuing stirring and vacuum degassing to obtain an epoxy / carbon nanotube coating; 10) coating the epoxy / carbon nanotube coating obtained in step 9) on the surface of the epoxy matrix obtained in step 6) to form a coating layer after filling the surface of the epoxy matrix, and placing the coating layer in an oven for multi-stage drying and curing to obtain an insulating material coated with epoxy / carbon nanotubes; The total mass percentage of the carbon nanotube particles, epoxy resin, anhydride curing agent and accelerator is 100%, wherein the mass fraction of the carbon nanotube particles is 0.15wt%.

2. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 1, characterized in that: In step 1), the preheating temperature of the carbon nanotube particles is 95°C to 105°C for 11h to 13h, and the particle size of the carbon nanotubes is 2nm to 20nm in diameter and 10um to 20um in length; the preheating temperature of the epoxy resin and the anhydride curing agent are both 50°C to 60°C for 6h to 8h, the epoxy resin adopts bisphenol A type liquid epoxy resin, and the anhydride curing agent adopts liquid methyltetrahydrophthalic anhydride.

3. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 2, characterized in that: In step 2), the mass fraction ratio of epoxy resin to methyltetrahydrophthalic anhydride curing agent is (98-102):(78-82).

4. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 3, characterized in that: In step 3), the heating temperature of the oil bath environment is 77° C. to 83° C., the heating time and stirring time are 37 min to 43 min, and the stirring speed is 77 rad / min to 83 rad / min.

5. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 4, characterized in that: In step 4), the mass fraction of the accelerator is 0.95% to 1.05% of the total mass fraction, the accelerator used is 2,4,6-tris(dimethylaminomethyl)phenol, the heating time and stirring time are 7min to 13min, and the stirrer speed is 77rad / min to 83rad / min.

6. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 5, characterized in that: The multi-stage heating procedure in step 5) is as follows: firstly heat to 77°C-83°C and keep warm for 3.9h-4.1h, then heat to 117°C-123°C and keep warm for 7.9h-8.1h. The mold used is a circular mold with a diameter of 49.9h-50.1h and a thickness of 0.99mm-1.01mm.

7. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 6, characterized in that: In step 7), the ultrasonic time is 1.9 h to 2.1 h, each ultrasonic time is 0.4 h to 0.6 h, and the interval between each ultrasonic time is 8 min to 12 min.

8. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 7, characterized in that: In step 8), the oil bath environment heating temperature is 77° C. to 83° C., the heating time and stirring time are 37 min to 43 min, and the stirring speed is 77 rad / min to 83 rad / min.

9. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 8, characterized in that: In step 9), the mass fraction of the accelerator is 0.95% to 1.05% of the total mass fraction, the accelerator used is 2,4,6-tris(dimethylaminomethyl)phenol, and the heating time and stirring time are 7 min to 13 min.

10. The method for preparing and coating a carbon nanotube modified coating for improving the surface flashover voltage of epoxy composite materials according to claim 9, characterized in that: The specific heating procedure in step 10) is: heating to 117° C. to 123° C. and keeping warm for 11.9 h to 12.1 h.

Citation Information

Cited By

  • Low-viscosity carbon nanotube reinforced epoxy resin system and preparation method thereof

    CN120737547A